Juridical study of the criminal act of defamation article 310 paragraph (1) of the Indonesian criminal law code (KUHP) - Muhamad yanto (Institute Of computer Science (IOCS), 2023)
The object of research as well as a problem in this research is the provision of criminal acts under Indonesian positive criminal law (KUHP), as well as the basis for judges deciding probation sentences against perpetrators of criminal offenses of Article 310 paragraph (1) of the Criminal Code.. Acts that offend honor in this sexual field do not include crime, decency or morality crimes referred to in Article 281 to Article 303 of the Criminal Code. The provisions of the defamation are stipulated in Chapter XVI concerning Insults, Book I specifically Articles 310, 311, 315, 317 and Article 318 of the Criminal Code. In addition to those stipulated in the Criminal Code, matters relating to